The Implementation of Character Building in English Language Teaching Activities - Dian Pertiwi Sari; aunurrahman aunurrahman; Dian Shinta Sari; Citra Kusumaningsih; Diah Astriyanti (XXXX-XXXX, 2022)
This qualitative research was conducted in order to analyze the implementation and the evaluation of character building in English language teaching activities at one of the private Islamic school in Pontianak. The subject of this research were active students at Seventh Grade and an English teacher. The sample was selected using a purposeful sampling technique. The technique of data collection applied were documentation, observation, and interview.  Documentation was used to get data from the lesson plan. Observation was used to get data in the process of teaching and learning activities. Meanwhile, an interview to get more information about character building that was implemented in the school. The results of this research showed from 18 character values based on curriculum, the values of religious, independent, communicative, social concern, discipline, curiosity, hard work, and respect for achievement are taught by teachers through teaching English in this school. Although, there were some character values from the lesson plan that were not implemented in the classroom, but most of the character values that were not in the lesson plan are taught by the teacher.